A review of the genus Oodescelis Motschulsky, 1845 (Coleoptera: Tenebrionidae: Platyscelidini) from China - Bai, Xing-Long; Li, Xiu-Min; Ren, Guo-Dong (Zootaxa, 2019)
The Chinese species of the genus Oodescelis Motschulsky, 1845 are revised. Fifteen species belonging to five subgenera are listed. O. (Acutoodescelis) emmerichi Kaszab, 1940 is proposed as subspecies of O. (A.) punctatissima (Fairmaire, 1886) [O. (A.) punctatissima emmerichi Kaszab, 1940, stat. n.]. A new synonym is established: O. (A.) pyripenis Ren, 1999 = O. (A.) punctatissima (Fairmaire, 1886), syn. n. based on the morphological characters, geographic distribution, and assessment on the molecular phylogeny [except O. (A.) pyripenis]. A new subspecies and a new species are described: O. (A.) punctatissima henanana Bai & Ren, subsp. nov. from Henan and O. (Planoodescelis) lii Bai & Ren, sp. nov. from Hubei. Lectotypes for the follwoing species are designated: Platyscelis punctatissima Fairmaire, 1886, Platyscelis (Oodescelis) affinis Seidlitz, 1893, Platyscelis (Oodescelis) brevipennis Kaszab, 1938, Platyscelis (Oodescelis) similis Kaszab, 1938, Oodescelis (Clavatoodescelis) acutanguloides Kaszab, 1940, Oodescelis (Clavatoodescelis) kuntzeni Kaszab, 1940 and Oodescelis (Clavatoodescelis) sachtlebeni Kaszab, 1940. Additional diagnostic characters of the subgenus Planoodescelis Egorov, 2004 are proposed. In addition, newly collected materials are examined, new distribution records, habitus of adults, images of male protibiae and aedeagus are provided, and a key to Chinese species is given. Furthermore, the first and preliminary molecular phylogeny of the genus is presented, and the used markers may be helpful to reconstitute the phylogenetic relations within the tribe Platyscelidini.